G-protein Signaling Components GCR1 and GPA1 Mediate Responses to Multiple Abiotic Stresses in Arabidopsis - Chakraborty, Navjyoti; Singh, Navneet; Kaur, Kanwaljeet; Raghuram, Nandula (Frontiers in Plant Science, 2015)
G-protein signalling components have been implicated in some individual stress responses in Arabidopsis, but have not been comprehensively evaluated at the genetic and biochemical level. Stress emerged as the largest functional category in our whole transcriptome analyses of knock-out mutants of GCR1 and/or GPA1 in Arabidopsis (Chakraborty et al., 2015a, PloS one 10, e0117819 and Chakraborty et al., 2015b, Plant Mol. Biol., doi: 10.1007/s11103-015-0374-2). This led us to ask whether G-protein signalling components offer converging points in the plant’s response to multiple abiotic stresses. In order to test this hypothesis, we carried out detailed analysis of the stress category in the present study, which revealed 144 differentially expressed genes (DEGs), spanning a wide range of abiotic stresses, including heat, cold, salt, light stress etc. Only 10 of these DEGs are shared by all the three mutants, while the single mutants (GCR1/GPA1) shared more DEGs between themselves than with the double mutant (GCR1-GPA1). RT-qPCR validation of 28 of these genes spanning different stresses revealed identical regulation of the DEGs shared between the mutants. We also validated the effects of cold, heat and salt stresses in all the 3 mutants and WT on % germination, root and shoot length, relative water content, proline content, lipid peroxidation and activities of catalase, ascorbate peroxidase and superoxide dismutase. All the 3 mutants showed evidence of stress tolerance, especially to cold, followed by heat and salt, in terms of all the above parameters. This clearly shows the role of GCR1 and GPA1 in mediating the plant’s response to multiple abiotic stresses for the first time, especially cold, heat and salt stresses. This also implies a role for classical G-protein signalling pathways in stress sensitivity in the normal plants of Arabidopsis. This is also the first genetic and biochemical evidence of abiotic stress tolerance rendered by knock-out mutation of GCR1 and/or GPA1. This suggests that G-protein signalling pathway could offer novel common targets for the development of tolerance/resistance to multiple abiotic stresses.